The Balanced Scorecard Logic in The Management Control and Reporting of Small Business Company Networks: A Case Study - Selena Aureli; Andrea Cardoni; Mara Del Baldo; Rosa Lombardi (Journal of Accounting and Management Information Systems (JAMIS), 2018)
The purpose of this paper is to assess and integrate the application of the balance scorecard (BSC) logic into business networks identifying functions and use that such performance measuring tool may undertake for SME's collaborative development. Thus, the paper analyses a successful case study regarding an Italian network of small companies, evaluating how the multidimensional perspective of BSC can support strategic and operational network management as well as communication of financial and extra financial performance to stakeholders. The study consists of a qualitative method, proposing the application of BSC model for business networks from international literature. Several meetings and interviews as well as triangulation with primary and secondary documents have been conducted. The case study allows to recognize how BSC network logic can play a fundamental role on defining network mission, supporting management control as well as measuring and reporting the intangible assets formation along the network development lifecycle. This is the first time application of a BSC integrated framework for business networks composed of SMEs. The case study demonstrates operational value of BSC for SME's collaborative development and success.
Keywords: M00; M41; M49; 650; management control; balanced scorecard; business networks